AN EPIDEMIOLOGICAL SURVEY OF OSTEOPOROTIC FRACTURES IN OLDER RESIDENTS FROM THE MIDDLE URALS - E. N. Gladkova; V. N. Khodyrev; O. M. Lesnyak (Научно-практическая ревматология, 2014)
The epidemiological characteristics of osteoporotic fractures in Russia have been inadequately studied.Objective: to estimate the incidence rate of osteoporotic fractures in the old age groups of an urban population in the Middle Urals.Subjects and methods. The survey was performed in Pervouralsk, a typical industrial town in the Middle Urals, with a total of 160,860 people, including 54,189 dwellers over 50 years of age (20,746 men and 33,443 women), which amounted to 33.7% of the general population of the town. The survey covered its residents aged 50 years and over who had fractures of the proximal hip (FPH), distal forearm (FDF), distal shin, ribs, or surgical neck of the humerusbetween 1 January 2008 and 31 December 2009. Statistical analysis was made applying the programs Biostatistics, Microsoft Excell 2007, and MedCalc (demo-version). The findings were processed using parametric and nonparametric statistical methods.Results. During two years, 1371 fractures, including FPH, FDF, fractures of the humerus, distal shin, and ribs, were registered in the examined sample of persons aged 50 years and over from Pervouralsk. 383 (27.9%) of these fractures occurred in men and 988 (72.1%) in women. The incidence rate of all fractures was 1265.0 per 100,000 inhabitants aged 50 years and over (1,477.1 for women and 923.1 for men). FDF were more common in women, the incidence was 787.9 cases per 100,000 population; costal fractures – in men (386.7 per 100,000). The investigation has shown that certain types of fractures are predominant in the oldest age groups. Thus, the incidence rate of FDF and fractures of the distal shin decreases while that of FPH and fractures of the humerus increaseswith age, which is likely to be due to several causes: an age-related decline in bone mass; an increase in the frequency of falls with age; muscle weakness and movement discoordination, which alter the mechanism of fall and increase the risk of femoral and humeral fractures.